# math

posted by .

7. Determine the inverse of each relation given.

a. f(x) = 1/x-2 + 3

b. f(x) = 2(x – 4)^2 + 5

• math -

y = 1/(x-2) + 3
y-3 = 1/(x-2)
x-2 = 1/(y-3)
x = 1/(y-3) + 2

so, f-1(x) = 1/(x-3) + 2

y = 2(x-4)^2 + 5
y-5 = 2(x-4)^2
(y-5)/2 = (x-4)^2
now, we can use ± root, so let's choose the + root:
√[(y-5)/2] = x-4
√[(y-5)/2]+4 = x

so, f-1(x) = √[(x-5)/2] + 4

## Similar Questions

1. ### Math

Let R1 be a binary relation on the set of integers defined as follows: R1 = {(x, y) / 4 divides x – y}. Determine whether the given relation R1 is an equivalence relation on the set {1, 2, 3, 4, 5}.
2. ### Math

Given f(x)=7-2(x-1)^2, x>= 1, determine f inverse (5).
3. ### Math

Given f(x)=7-2(x-1)^2, x>= 1, determine f inverse (5).
4. ### algebra

Determine whether the following relation represents a function. If the relation is a function then state domain and range?
5. ### Math Questions

1.) What is the inverse of the relation (3, -1), (2. 5), (-4, -4)?
6. ### Math

1.) What is the inverse of the relation (3, -1), (2. 5), (-4, -4)?
7. ### Algebra 2

what is the inverse of the given relation?
8. ### Algebra2

Does the relation in the table represent direct variation inverse variation or neither?
9. ### algebra

what is the inverse of the given relation?
10. ### Math

Does the relation in the table represent direct variation, inverse variation, or neither?

More Similar Questions